Predictors of Linear and Multidirectional Acceleration in Elite Soccer Players. Issue 2 (February 2019) - Northeast, Jonathan; Russell, Mark; Shearer, David; Cook, Christian J.; Kilduff, Liam P.
Abstract : Abstract: Jonathan, N, Russell, M, Shearer, D, Cook, CJ, and Kilduff, LP. Predictors of linear and multidirectional acceleration in elite soccer players. J Strength Cond Res 33(2): 514–522, 2019—Linear and multidirectional acceleration underpins success in professional soccer match play. However, the physical qualities that determine these performance indicators are poorly understood in elite players. English Premier League players ( n = 26) performed isometric midthigh pulls (IMTPs), bilateral and unilateral drop jumps (from 40 and 20 cm, respectively), bilateral and unilateral countermovement jumps (CMJs), and assessments of linear (5, 10, and 20 m) and multidirectional (left and right preplanned and reactive) acceleration. Regression analyses highlighted that 21% of variance in 5-m sprint time (1.02 ± 0.07 seconds) was explained by relative peak power output (PPO) in bilateral CMJ (54.5 ± 5.3 W·kg −1 ). A 5.4 W·kg −1 increase in CMJ predicted a 0.03-second decrease in 5-m sprint time ( P = 0.02). For 10-m sprint time (1.72 ± 0.09 seconds), 44% of variance was explained by isometric relative peak force ([PF]; 30.4 ± 4.9 N·kg −1 ) and bilateral relative CMJ PPO (54.5 ± 5.3 W·kg −1 ). A 5.4 W·kg −1 increase in CMJ predicted reduced 10-m sprint times by 0.04 seconds ( P = 0.01). For 20-m sprint time (2.94 ± 0.11 seconds), 55% of the total variance was explained by isometric relative PF (30.4 ± 4.9 N·kg −1 ) and relative CMJ PPO (54.5 ± 5.3 W·kg −1 ). Increases of 5.4 W·kg −1 in bilateral CMJ predicted an improvement of 20-m sprint time by 0.06 seconds ( P = 0.002). Contributions were insignificant ( P > 0.05) for preplanned and reactive multidirectional acceleration. Relativized indices, especially those related to force production during CMJ and IMTP tests, likely underpin linear but not multidirectional acceleration performance in professional soccer players. When linear acceleration is a training focus, practitioners should seek to monitor CMJ and IMTP test performance.